Allosteric activation of PP2A inhibits experimental abdominal aortic aneurysm. Issue 17 (17th September 2021) - Zhou, Xianming; Zhang, Chao; Xie, Fei; Wei, Wei; Li, Rui; Xu, Qian; Wang, Yu; Klenotic, Philip A.; Narla, Goutham; Dong, Nianguo; Lin, Zhiyong
Abstract: Although extremely important, the molecular mechanisms that govern aortic aneurysm (AA) formation and progression are still poorly understood. This deficit represents a critical roadblock toward the development of effective pharmaceutical therapies for the treatment of AA. While dysregulation of protein phosphatase 2A (PP2A) is thought to play a role in cardiovascular disease, its role in aortic aneurysm is unknown. The objective of the present study is to test the hypothesis that PP2A regulates abdominal aortic aneurysm (AAA) progression in a murine model. In an angiotensin II-induced AAA murine model, the PP2A inhibitor, LB-100, markedly accelerated AAA progression as demonstrated by increased abdominal aortic dilation and mortality. AAA progression was associated with elevated inflammation and extracellular matrix fragmentation, concomitant with increases in both metalloproteinase activity and reactive oxygen species production. Conversely, administration of a novel class of small molecule activators of PP2A (SMAPs) resulted in an antithetical effect. SMAPs effectively reduced AAA incidence along with the corresponding pathologies that were increased with LB-100 treatment. Mechanistically, modulation of PP2A activities in vivo functioned in part via alteration of the ERK1/2 and NFκB signaling pathways, known regulators of AAA progression. These studies, for the first time, demonstrate a role of PP2A in AAA etiology and demonstrate that PP2A activation may represent a novel strategy for the treatment of abdominal aortic aneurysms.